Physicochemical properties of chickpea hull and corn bran gums - M, Vázquez-Banda; Cauich J.G, Dzul-; Vieyra M.I., García (Emirates Journal of Food and Agriculture, 2023)
Currently, there is increasing interest on natural hydrocolloids such as gums. In the present work, the solubility, zeta potential and rheological properties of gums from chickpea hull and corn bran were studied. Chickpea hull and corn bran gums were extracted from chickpea hulls and nejayote, respectively. The chickpea hull gum had 2.98% of protein (w/w) and corn bran gum 2.28% (w/w), an ash content of 2.25% (w/w) and 6.21% (w/w), respectively. Chickpea hull gum (CHG) had its highest solubility (above 50%) at 50 °C and 12 hours. Corn bran gum showed a solubility over 90% at 12 hours at 25 °C. The Zeta potential values for both gums were negative (from -0.33 mV to -20.0 mV) through the pH range studied (from 2.0 to 7.0). The dispersions of both gums showed a rheological behavior in which viscosity decreases when increasing the shear rate from 10-2 s-1 to 103 s-1 for chickpea hull gum and corn bran gum at 2%; the rheological viscosity values of the dispersions was adjusted to the Carreau-Yasuda model. Keywords: Gums; Solubility; Zeta Potential; Viscosity; Shear-thinning